Eksperimen Pembelajaran Matematika Melalui Model Auditory Intellectually Repetition (Air) Dan Direct Instruction (Di) Ditinjau Dari Self-Efficacy Matematis Siswa Kelas VIII SMP Muhammadiyah 1 Surakarta 2015/2016 - NUR WIDIANSARI, FATKHIYAH; , Rita P. Khotimah, S.Si., M.Sc (2016)
This study aims to examine: (1) the effect of Auditory Intellectually Repetition (AIR) model and the Direct Instruction (DI) model toward the mathematics learning outcomes; (2) the effect of student's mathematical self-efficacy toward mathematics learning outcomes; (3) the effect of the interaction between the learning models of Auditory Intellectually Repetition (AIR) and Direct Instruction (DI) along with student's mathematical self-efficacy toward mathematics learning outcomes. This experiment was conducted to the students of grade of even semester academic year 2015/2016 at SMP Muhammadiyah 1 Surakarta with the population of all eighth grade students. This research was quantitative with quasi-experimental research design. The classes that become the sample in this study were taken with cluster random sampling method. The methods used in data collection using test, questionnaire, and documentation. Data were analyzed using analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there is effect from Auditory Intellectually Repetition (AIR) and the Direct Instruction (DI) learning models toward the mathematics learning outcomes; (2) there is no effect of student's mathematical self-efficacy toward the mathematics learning outcomes; (3) there is no interaction effect between Auditory Intellectually Repetition (AIR) and the Direct Instruction (DI) learning models along with mathematical self-efficacy toward mathematics learning outcomes.